2007
DOI: 10.1111/j.1365-2249.2007.03350.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo treatment with the herbal phenylethanoid acteoside ameliorates intestinal inflammation in dextran sulphate sodium-induced colitis

Abstract: SummaryRecently we demonstrated that in inflammatory bowel disease (IBD) macrophage-oxidative burst activity is increased and NADPH oxidase mRNA is induced. The herbal phenylethanoid acteoside isolated from Plantago lanceolata L. was shown to exhibit anti-oxidative potential. Using the dextran sulphate sodium (DSS)-induced colitis model, in this study we have assessed whether systemic application of acteoside affects colitis. Colitis was induced by DSS in Balb/c mice. Treatment with acteoside (120, 600 mg/ mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(85 citation statements)
references
References 27 publications
1
83
0
1
Order By: Relevance
“…20 Furthermore, antioxidant administration can reduce mucosal inflammation in IBD. 21 These studies indicate that part of the treatment efficacy of drugs used in the treatment of IBD could be mediated by decreasing the production or effects of ROS. 22 Such information could contribute to future developments in anti-inflammatory therapy.…”
Section: Discussionmentioning
confidence: 99%
“…20 Furthermore, antioxidant administration can reduce mucosal inflammation in IBD. 21 These studies indicate that part of the treatment efficacy of drugs used in the treatment of IBD could be mediated by decreasing the production or effects of ROS. 22 Such information could contribute to future developments in anti-inflammatory therapy.…”
Section: Discussionmentioning
confidence: 99%
“…22 Severity of the colitis was assessed by an established scoring system as published before. 23 For immunohistochemical analysis, the following primary antibodies were used: Sdc1 (rat anti-mouse Sdc1 mAb clone 281-2, diluted 1/100 in PBS with 1% BSA; BD Pharmingen, Heidelberg, Germany), Sdc2 (rabbit-antimouse, diluted 1/50; Santa Cruz Biotechnology, Santa Cruz, CA), Sdc3 (rat-anti-mouse mAb clone 312607, diluted 1/50; R&D Systems, Wiesbaden, Germany), Sdc4 (ratanti-mouse clone KY/8.2, diluted 1/50; BD Pharmingen), F4/80 (rat-anti-mouse, clone BM8; eBioscience, San Diego, CA), CD4, CD8, and B220 (rat anti-mouse, clone C3T4 (CD4), clone 53-6.7 (CD8), and clone RA3-6B2 (B220), diluted 1/100; BD Pharmingen). M cells were stained with the UEA1 lectin method (Sigma-Aldrich, Deisenheim, Germany) as described elsewhere.…”
Section: Histological Examinationmentioning
confidence: 99%
“…23 Briefly, inflammatory activity was characterized by the severity of inflammatory damage and destruction of cytoarchitecture of the gut (loss of epithelial cells (grade 1) On day 9, placebo-treated Sdc1 KO mice showed a strong epithelial disintegration with ulcerations, edema, muscular thickening, and wide areas of epithelial denudation; nearly no intact mucosa was seen (Figure 2A). Colonic tissue from placebo and enoxaparin-treated wildtype mice had less severe signs of epithelial damage with ulcerations and edema; epithelial healing on day 9 was detectable.…”
Section: Enoxaparin Treatment Improves Intestinal Wound Healing In Sdmentioning
confidence: 99%
See 1 more Smart Citation
“…Penido et al, revealed that 121 exhibited a potent inhibitory effect on LPS-induced total leucocyte, neutrophil and eosinophil accumulation in the pelural cavity along with a potent antiulcerogenic activity against diclofenac-induced gastric ulcers at 100 mg/kg [84]. Meanwhile, the histological scores indicated that treatment with 121 ameliorated intestinal inflammation in both acute and chronic dextran sulphate sodium-induced colitis in vivo through inhibition of oxidative burst activity [85]. Cell adhesion molecules (CAMs) play a role in the pathogenesis of atherosclerosis and inflammation.…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%